Identification of novel survivin interactors - Alhawsawi, Naif (2024)
Survivin, a multifaceted protein, plays crucial roles in various cellular processes, including apoptosis inhibition, mitosis, autophagy, and mitochondrial dynamics.Its overexpression has been linked to cancer cell proliferation, angiogenesis, chemotherapy resistance, and poor prognosis in multiple sclerosis. While primarily known for its roles in programmed cell death and cell division, recent evidence suggests its involvement in clathrin-mediated endocytosis trafficking. To explore survivin's interactions and potential functions, we conducted protein-protein interaction studies. We identified two novel interactors, AP1g1 and Seh1, and confirmed a previously reported interaction with CHC. Our findings indicate that survivin directly interacts with AP1g1 and Seh1, while its interaction with CHC is indirect. Additionally, we observed that survivin overexpression downregulates the expression of CNP and PDGFR-a, two myelin-related genes regulated by Seh1 indicating a potential survivin role.These results collectively suggest that survivin may play a role in trafficking and in regulating the myelination of the central nervous system.